Projecting the Occupational Structure of Employment in OECD Countries - Hughes, Gerald (OECD Labour Market and Social Policy Occasional Papers, 1993)
Forecasts of employment by occupation have been made in several OECD countries since the early 1950s. Medium to long-term projections are now made in most OECD countries, and a number of countries publish them regularly. This paper by Gerald Hughes, of the Economic and Social Research Institute, Dublin, examines how their objectives, methods and uses have changed over the last three decades. It covers technical issues such as the standard method of projection using statistics for employment cross-classified by industry and occupation, the integration of information from other sources such as surveys of employer expectations, the confrontation of employment forecasts with separate models of labour supply, and the competing "rate of return" approach to investment in human capital. It also considers management issues such as the institutional status of the bodies that make forecasts, and methods of disseminating the results to training institutions, career advisers and other users